Complete genome analysis of Vibrio mimicus strain SCCF01, a highly virulent isolate from the freshwater catfish. Issue 1 (1st January 2020) - Yu, Zehui; Wang, Erlong; Geng, Yi; Wang, Kaiyu; Chen, Defang; Huang, Xiaoli; Ouyang, Ping; Zuo, Zhicai; Huang, Chao; Fang, Jing; Yin, Lizi; Guo, Hongrui; et al.
ABSTRACT: Vibrio mimicus is a foodborne pathogen, which is widely distributed in the aquatic environment. Moreover, it is often involved in aquatic animal diseases. In recent years, V. mimicus is an emerging pathogen in some species of Siluriformes. The strain SCCF01 was isolated from yellow catfish ( Pelteobagrus fulvidraco ). In this study, we aimed to perform genomic analysis of V. mimicus strain SCCF01 to identify genetic features and evolutionary relationships. Information on gene function and classification was obtained by functional annotation, and circular graph of strain SCCF01 genome, which was created by Circos v0.64. Information on virulence genes (adhesion, flagellum system, exotoxin, and secretory system, etc.) was obtained by virulence genes annotation. Genome element prediction showed that most of the mobile elements were distributed in chromosome I. Therefore, chromosome I of SCCF01 genome has more plasticity than chromosome II and might be larger in size. Genomic linear relationship between the strain of V. mimicu s and strain SCCF01 was analyzed by linear pairwise comparison but was unable to determine the relationship. Gene family analysis predicted that the evolutionary direction of strain SCCF01 was: clinical strain → environmental strain → SCCF01 strain. Phylogenetic analysis showed that the strain SCCF01 was more closely related to environmental strains. According to gene family analysis and phylogenetic analysis, we speculated that strain SCCF01 has probably diverged from environmental strains.